Decreased production in broiler breeders due to tendon rupture by Mycoplasma synoviae - MOREIRA, F. A.; CARDOSO, L.; COELHO, A. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
An outbreak of lameness occurred in a broiler breeder flock (30,000 birds into four houses) of a multi-age farm, with a total of two broiler breeder flocks (60,000 birds in total). The leg lesions began soon after facilities transfer between 22 and 24 weeks of age and persisted for the rest of the flock’s life, until 64 weeks of age. Post-mortem examination at the farm revealed arthritis lesions and synovitis affecting the hock joint and the foot pads. Mycoplasma synoviae was detected in birds from the affected flock by serologic and molecular techniques. Treatments with fluoroquinolones in drinking water reduced the number of cases, but morbidity continued and affected the standard production rates.